Below-Ground Interactions in Tropical Agroecosystems: Concepts and Models With Multiple Plant Components 2004
DOI: 10.1079/9780851996738.0017
|View full text |Cite
|
Sign up to set email alerts
|

Locally derived knowledge of soil fertility and its emerging role in integrated natural resource management.

Abstract: This paper discusses the terminology and approaches that surround research on local knowledge, which reveal important differences in the emphasis of research following anthropological, as opposed to natural science, traditions. Results from three case studies undertaken in Nepal, Ghana and Indonesia were used to illustrate key points about local knowledge concerned with soil classification, soil fertility and below-ground interactions. Local knowledge of soils can be useful in agricultural development through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…In Southeast Sulawesi, respondents described the root structure of rambutan and langsat trees as "long," "strong," "shallow," or "spreading," in line with existing literature (Watson 1982, Calvo 1994, van Noordwijk and Purnomosidhi 1995. Smallholders tend to associate visible root systems with an increase in resource competition between shade trees and crops, as has been documented previously in both Java (Joshi et al 2000) and Nepal (Joshi et al 2004). Farmers might also underestimate the extent to which rambutan or durian can improve soil indicators that we used to assess soil fertility.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In Southeast Sulawesi, respondents described the root structure of rambutan and langsat trees as "long," "strong," "shallow," or "spreading," in line with existing literature (Watson 1982, Calvo 1994, van Noordwijk and Purnomosidhi 1995. Smallholders tend to associate visible root systems with an increase in resource competition between shade trees and crops, as has been documented previously in both Java (Joshi et al 2000) and Nepal (Joshi et al 2004). Farmers might also underestimate the extent to which rambutan or durian can improve soil indicators that we used to assess soil fertility.…”
Section: Discussionsupporting
confidence: 76%
“…This has been the case in other regions where farmers were acutely aware of processes directly tied to crop productivity, such as the risk of physical damage caused to cocoa trees by falling branches from shade trees (Atkins andEastin 2012, Lamond et al 2016) or the appearance of yellow leaves, which are indicative of poor cocoa tree health and can be expected to lead to decreased productivity (Isaac et al 2009). Similarities in farmer perceptions regarding physical soil properties (Joshi et al 2004) and the usefulness of shade trees in coffee or cocoa agroforests (Albertin and Nair 2004, Anglaaere et al 2011, Gyau et al 2014 have been observed across different regions. Such commonalities in the ways cocoa farmers across the globe relate soil fertility and cocoa tree health highlight that indicators used by farmers vs. scientists do not always capture the same things, and underline the importance of local knowledge.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Since the 1980s, the predominant trend has been for participatory approaches to replace more formal farming systems research, with the systems understanding and local knowledge becoming increasingly implicit, through the involvement of farmers in the research process (Farrington 1988;Pretty 1995). In contrast, research on broader aspects of natural resource management has embraced a systems approach (Sayer and Campbell 2004) and explicit treatment of local knowledge (Sinclair and Walker 1998;Joshi et al 2004) but tended to increasingly focus at landscape scales consistent with consideration of a range of ecosystem services manifest at these scales Cerdan et al 2012). At the same time, the focus of farmer participatory research has broadened to encompass a wider concept of innovation systems that includes markets and the institutional context within which innovation occurs (Scoones and Thompson 2009;Kilelu et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This means that knowledge that enters a locality is not simply internalized, but becomes transformed by various actors to suit their circumstances. According to Joshi et al (2004), knowledge continuously evolves as farmers learn both by evaluating the outcomes of previous actions and by observing the environment. In the study presented here, improved fallows and biomass transfer technologies were introduced to address the problem of soil fertility in western Kenya.…”
Section: Knowledge Generation By Farmersmentioning
confidence: 99%